2013
DOI: 10.1063/1.4813672
|View full text |Cite
|
Sign up to set email alerts
|

Strain hardening and jump-like deformation of ultrafine polycrystalline Al-Li solid solutions at 0.5 K

Abstract: This is a study of the effect of microstructure created by severe plastic deformation (SPD) and annealing on strain hardening and jump-like deformation in Al-Li alloys. It is shown that under tension at 0.5 K, SPD processed polycrystals retain a significant strain hardening rate and have high strength and ductility. SPD also simulates unstable (jump-like) flow of the polycrystals owing to dislocation dynamics that shows up as stress jumps in the tension curve. The average amplitude of the jumps increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In the discussion of the discontinuous flow we will take into account that the plastic deformation of crystals is intrinsically discrete due to its dislocation nature and heterogeneous internal stress. Therefore, an individual avalanche from several dozens of dislocations can originate in the region of stress concentrations, for example, in the head of the dislocation pile-up near a sessile (Frank) dislocation [1,[3][4][5]. In the case of collapse of this sessile configuration a local excess of mobile dislocations generates a local strain event usually accompanied by the acoustic emission events [4,9,10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussion of the discontinuous flow we will take into account that the plastic deformation of crystals is intrinsically discrete due to its dislocation nature and heterogeneous internal stress. Therefore, an individual avalanche from several dozens of dislocations can originate in the region of stress concentrations, for example, in the head of the dislocation pile-up near a sessile (Frank) dislocation [1,[3][4][5]. In the case of collapse of this sessile configuration a local excess of mobile dislocations generates a local strain event usually accompanied by the acoustic emission events [4,9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that the scale and the statistics of stress jumps depend on the type of the crystal lattice, the shape, the defect structure and the electronic state of the specimen, as well as on other factors that affect the evolution of the dislocation system and determine the strain hardening rate of the material. Recently the study of the nature of LTJD has been closely associated with the development of methods of severe plastic deformation, which makes it possible to investigate the discontinuous flow of polycrystals with a substantially altered microstructure [5]. * corresponding author; e-mail: janecek@met.mff.cuni.cz…”
Section: Introductionmentioning
confidence: 99%
“…существует связь между поведением дислокаций (их движением, накоплением у препятствий) и модулем пластичности. в частности, чем больше модуль пластичности, тем быстрее накапливаются дислокации и тем выше чувствительность материала к концентрации напряжений [8,9]. модуль пластичности (коэффициент упрочнения) определяли с использованием методов моделирования в программной среде StatSoftStatisticaV6.0 (табл.…”
Section: к л ю ч е в ы е с л о в а : электроконтактная наплавка струunclassified